Conventional Control vs. Robust Control on Heat-exchangers. (2015) - Dulău, Mircea; Oltean, Stelian; Gligor, Adrian
Abstract: This paper presents the basic concepts of the conventional and robust control design applied on heat-exchanger (HE), which is described by a second order mathematical model with delay time. Two time constant of the transfer function are considered with their nominal values and affected by uncertainties and the proportional factor contain un-modelled dynamics, all expressed as a percentage. The controllers are tuned by Zeigler-Nichols experimental criteria and by H-infinite (H∞ ) synthesis and then the most significance performances of these are presented. Using Matlab software facilities, have been simulated the frequency characteristics of sensitivities functions and the temperature time response in close-loop connection with the designed controllers.